Pengembangan Media Pembelajaran Fisika Berbantuan Aplikasi Smart Apps Creator Untuk Meningkatkan Pemahaman Konsep Peserta Didik - Watin, Wisnu; Gunada, I Wayan; Ayub, Syahrial; Wahyudi, Wahyudi (Universitas Hamzanwadi, 2023)
This development research aims to produce products in the form of physics learning media assisted by smart apps craeator applications with the final product results in the form of feasible, practical, and effective applications to improve students' understanding of concepts. The product developed is physics learning media created using the smart apps creator application. The type of research used is Research and Development using the 4D stages proposed by Thiagarajan. The stages of this research are (1) Define; (2) Design (design); (3) Develop; Disseminate (dissemination). The research subjects were 3 lecturers of Physics Education FKIP Unram and a physics teacher of SMAN 1 Gunungsari as validators, and 26 students of grade XI Science 3 as field test subjects. The average results of learning media validation scores based on the assessment of expert validators and practitioner validators are in the very good category. The average PA (Percentage of Agreement) for each component of learning devices and media is more than 75% with the reliable category. The results of N-Gain acquisition in aspect 7 aspects, namely interpreting, exemplifying, classifying, summarizing, inferring, comparing, explaining) obtained a result of 0.8 in the high category. The results of student responses showed a percentage of 89% in the very practical category. Thus, it can be concluded that physics learning media assisted by smart apps creator applications on mechanical wave characteristic materials are feasible, effective, and practical to improve students' understanding of concepts.